Aktywność edukacyjna seniorów na przykładzie uniwersytetów trzeciego wieku w województwie świętokrzyskim - Renata Miszczuk; Andrzej Kobiałka (Edukacja Ustawiczna Dorosłych)
The goal of this work is to present the educational activity among the elderly in Poland with the particular emphasis on the activity in the Universities of the Third Age. General assumptions of active ageing and the scope of activities of Universities of the Third Age will given an overview. Finally, the psychosocial needs of seniors will be presented. On the basis of analyses the authors tried to answer the question what role do Third Age Universities play in the educational activation of the elderly.